The social costs of health-related early retirement in Germany: Evidence from the German Socio-economic panel - Gisela Hostenkamp; Michael Stolpe (Kiel Institute for the World Economy (IfW), 2008)
This study investigates the role of stratification of health and income in the social cost of healthrelated early retirement, as evidenced in the German Socio-economic Panel (GSOEP). We interpret early retirement as a mechanism to limit work-related declines in health that allows poorer and less healthy workers to maximize the total discounted value of annuities received from Germany's pay-as-you-go pension system. Investments in new medical technology and better access to existing health services may help to curb the need for early retirement and thus improve efficiency, especially amid population ageing. To value the potential gains, we calibrate an intertemporal model based on ex post predictions from stratified duration regressions for individual retirement timing. We conclude that eliminating the correlation between income and health decline would delay the average age of retirement by approximately half a year, while keeping all workers in the highest of five categories of self assessed health would yield a further delay of up to three years. Had this scenario been realized during our 1992?2005 sample period, we estimate the social costs of early retirement would have been more than 20 percent lower, even without counting the direct social benefits from better health.
Keywords: H55; I12; O15; 330; Health inequality; Social costs; Medical technology; Calibration; Retirement timing; Flexible Altersgrenze; Erwerbsunfähigkeit; Gesundheitsvorsorge; Medizin; Technischer Fortschritt; Soziale Kosten; Deutschland